2003
DOI: 10.3168/jds.s0022-0302(03)73939-3
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: DNA Typing for Ovine MHC DRB1 Using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP)

Abstract: The ovine major histocompatibilty complex (Ovar) class II DRB1 second exon was amplified by polymerase chain reaction (PCR) from DNA samples of 52 Suffolk sheep. Polymerase chain reaction products were characterized by the restriction fragment length polymorphism (RFLP) technique using nine restriction enzymes, RsaI, HaeIII, SacI, SacII, DdeI, NciI, Hin1I, EcoRI, and BstNI, yielding 13 types. Sequencing of cloned PCR products identified 16 Ovar-DRB1 alleles. Collectively, all PCR-RFLP patterns exactly matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 21 publications
6
50
0
Order By: Relevance
“…Alleles found in this study were similar to those previously identified and reported by Konnai et al (2003) and Amills et al (1996). Although novel alleles were not identified, further detailed DNA sequence analysis of the exon 2 regions of Ovar-DRB1 and Ovar-DRB3 from Turkish sheep breeds will be carried out.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Alleles found in this study were similar to those previously identified and reported by Konnai et al (2003) and Amills et al (1996). Although novel alleles were not identified, further detailed DNA sequence analysis of the exon 2 regions of Ovar-DRB1 and Ovar-DRB3 from Turkish sheep breeds will be carried out.…”
supporting
confidence: 65%
“…Although novel alleles were not identified, further detailed DNA sequence analysis of the exon 2 regions of Ovar-DRB1 and Ovar-DRB3 from Turkish sheep breeds will be carried out. (Amills et al 1996;Konnai et al 2003;Dongxiao & Yuan 2004;Gruszczynska et al 2005;Brujeni et al 2009). To date, 106 Ovar-DRB1 alleles have been identified by DNA sequencing of exon 2 from various breeds of sheep (Schwaiger et al, 1995;Schwaiger et al, 1996;Jugo & Vicario, 2000;Konnai et al, 2003;Ballingall et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The MHC of sheep is known as Ovar ('Ovar' representing Ovis aries) and is located on chromosome 20. The Ovar class II genes encode polymorphic glycoproteins composed of 9 covalently linked subunits (α and β subunits) that play a pivotal role in the initiation of the immune response against pathogen-derived peptide antigens (11). Among Ovar class II genes, the expressed DRB1 locus has been found to be highly polymorphic, and most of the polymorphic sites on DRB1 are located in exon 2, which encode the outer domain of MHC, especially the β-chain, which is the binding site for an antigen (11,12).…”
Section: Introductionmentioning
confidence: 99%